The effect of glass waste on climate change - Ignatia Marlin Pongoh; Yunita Ismail Masjud (Environment Conflict, 2024)
Currently, a lot of Glass Waste is scratted everywhere. This happens with the increasing use of glass objects for building needs or household appliances. Glass Waste is waste that is considered dangerous if it is disposed of in any place, because it is feared that it will be stepped on or injure other parts of the human body. As we know, Glass Waste is also very difficult to decompose in the soil, and it takes hundreds of years to decompose. Because Glass is not biodegradable substance, landfill are not an environmentally responsible way to dispose of it. As a result, efficient waste glass management is quite important. Scattered Glass Waste will only add to the problem for the environment, and even worse, it will affect climate change. Climate change will result in many negative things for humans and the environment.